Potential applications of porphyrins in photodynamic inactivation beyond the medical scope - Alves, Eliana (2017)
Although the discovery of light-activated antimicrobial agents had been reported in the 1900s, only more recently research work has been developed toward the use of photodynamic process as an alternative to more conventional methods of inactivation of micro(organisms). The photoprocess causes cell death through irreversible oxidative damage by reactive oxygen species produced by the interaction between a photosensitizing compound and a light source. With great emphasis on the environmental area, photodynamic inactivation (PDI) has been tested in insect eradication and in water disinfection. Lately, other studies have been carried out concerning its possible use in aquaculture waters or to the control of food-borne pathogens. Other potential applications of PDI in household, industrial and hospital settings have been considered. In the last decade, scientific research in this area has gained importance not only due to great developments in the field of materials chemistry but also because of the serious problem of the increasing number of bacterial species resistant to common antibiotics. In fact, the design of antimicrobial surfaces or selfcleaning materials is a very appealing idea from the economic, social and public health standpoints. Thus, PDI of micro(organisms) represents a promising alternative. In this review, the efforts made in the last decade in the investigation of PDI of (micro)organisms with potential applications beyond the medical field will be discussed, focusing on porphyrins, free or immobilized on solid supports, as photosensitizing agents.